Early complications and prognosis with multiple organ system failure score - Das, Kaushik; Shaikh, Junaid M.; Potey, Ketika; Jadhav, Sarojini P. (International Surgery Journal, 2021)
Background: Acute pancreatitis is a common surgical entity with a wide clinical spectrum ranging from mild pancreatitis to severe acute pancreatitis with lethal complications. A number of scoring systems have been devised to predict and manage complications associated with severe acute pancreatitis. The objective of this study was to study the demographics, early complications of acute pancreatitis with their outcome, and to assess the efficacy of multi organ system failure score. Methods: This was a descriptive study including 120 patients of acute pancreatitis done over a period of 2 years. The management of complications and their outcome were recorded in detail. A multi organ system failure score was used to predict and assess the severity of acute pancreatitis. Results: Total 120 patients were evaluated with mean age of 40 years and male preponderance. Alcohol consumption was the most common etiological factor. Acute fluid collection was the most common local complication while shock was the most common systemic complication. MOSF scoring system had a sensitivity, specificity and positive predictive value of 96%, 92.8% and 90.5% respectively. Mortality was 5.8% seen in patients with MOSF score above 5. Conclusions: The management of early complications of acute pancreatitis is mainly conservative, with surgical management limited to only a few selected patients. MOSF score is a valuable tool to predict and assess the severity of acute pancreatitis and should be used for monitoring of high risk patients.